2003
DOI: 10.1074/jbc.m302579200
|View full text |Cite
|
Sign up to set email alerts
|

Human Prorenin Has “Gate and Handle” Regions for Its Non-proteolytic Activation

Abstract: Prorenin is the inactive precursor of renin (EC 3.4.23.15), which is a key enzyme in the regulation of blood pressure and electrolyte balance. Prorenin has a prosegment with 43 residues attached to the N terminus of mature renin with 339 -341 residues (1-4). The prosegment has been considered to associate with mature renin to prevent interaction with angiotensinogen, its macromolecular renin substrate (5-7). Prorenin does not proteolytically self-activate like pepsinogen, and its blood circulating level is 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
184
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(188 citation statements)
references
References 31 publications
1
184
0
1
Order By: Relevance
“…HRMECs were cultured following the manufacturer's instructions. To cover the handle region of the prorenin molecule, which is the binding site of (P)RR [23], we synthesised decoy peptides NH 2 -RIFLKRMPSI-COOH as a human (P)RR blocker (PRRB), and purified them by high-pressure liquid chromatography on a C-18 reversephase column. After being serum deprived, cells were pretreated with 1 μmol/l PRRB for 1 h or 10 μmol/l MAPK/ ERK kinase (MEK) inhibitor U0126 (Promega, Madison, WI, USA) for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…HRMECs were cultured following the manufacturer's instructions. To cover the handle region of the prorenin molecule, which is the binding site of (P)RR [23], we synthesised decoy peptides NH 2 -RIFLKRMPSI-COOH as a human (P)RR blocker (PRRB), and purified them by high-pressure liquid chromatography on a C-18 reversephase column. After being serum deprived, cells were pretreated with 1 μmol/l PRRB for 1 h or 10 μmol/l MAPK/ ERK kinase (MEK) inhibitor U0126 (Promega, Madison, WI, USA) for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…10 On the basis of this finding, the 'handle region' of prorenin prosegment was thought to be a candidate of the prorenin site binding (P)RR. This concept was recently confirmed by the study using the BIACORE method showing that a peptide corresponding to the 'handle region' (HRP) binds to the (P)RR and that pretreatment with HRP inhibits the prorenin binding to the (P)RR.…”
Section: Suggestions From Animal Models Of Diabetesmentioning
confidence: 99%
“…Also, the data obtained from the BIAcore kinetic study showed that the association rate of prorenin to (P)RR is higher than that of mature renin (1.8Â10 7 and 2.16Â10 6 M À1 s À1 , respectively). 44,45 HRP/DECOY AND 'HINGE' REGION PEPTIDES ARE THE MOST PROBABLE CANDIDATES FOR (P)RR BLOCKER The decoy peptide mimics the R 10P IFLKRMPSI 19P region of prorenin prosegment was first indicated by Ichihara et al 30 who designed this peptide based on the 'handle' region peptide (HRP, I 11P FLKR 15P ) in prorenin prosegment reported by Suzuki et al 24 Ichihara et al 30 demonstrated complete inhibition of diabetic nephropathy by administering this peptide in the streptozotocin-induced diabetic rats. After that, many in vivo studies have investigated the effective use of the decoy containing 'handle' region peptide as (P)RR blocker and confirmed the regression of established diabetic nephropathy in heminephrectomized streptozotocin-induced diabetic rats; 46 attenuation of the development and progression of proteinuria and glomerulosclerosis and reduction of renal angiotensin levels in stroke-prone spontaneously hypertensive rats without an effect on blood pressure; 47 attenuation of cardiac fibrosis in spontaneously hypertensive rats fed on a high-salt diet.…”
Section: Cos-7 Cellsmentioning
confidence: 99%
“…22,23 Also, the 'gate' (T 7P FKR 10P ) and 'handle' (I 11P FLKR 15P ) regions in the prorenin prosegment were indicated in vitro to be accountable for the non-proteolytic activation of prorenin molecules through protein-protein interaction. 24 The (pro)renin receptor, 25 (P)RR, a new player in the RAS components, binds both renin and prorenin. [25][26][27][28][29] The (P)RR itself has been observed to be associated with many pathophysiology of diseases.…”
Section: Introductionmentioning
confidence: 99%